A natural resource management framework for sustainable development - Suleman Aziz Lodhi; Muhammad Abdul Majid Makki (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2010)
Natural resources in the form of oil, gas, minerals and forests are an asset in the countries where they are found. A number of countries depend largely on exports of their natural resources, earning major portion of their foreign exchange from these exports. It is very easy for the countries to exhaust their natural resources by over utilization of these resources. Policy makers may overlook sustainability aspect of the natural assets and resultantly, design policies to obtain short term gains while ignoring long term implications. Another problem faced by countries depending heavily on export of natural resources is that their revenue generation capacities from service sector or export of other items is overlooked in policy decisions. The paper presents a framework that may be used by policymakers for visualizing country's natural resources as assets and developing policies for gaining maximum economic benefits from these assets, but at the same time, taking care that these assets are developed and preserved for the next generations. The paper suggests that the countries should view natural resources as critical asset and secondly, asset specific strategies should be formed for their development. It is emphasized that these asset specific strategies should be designed in such a manner as they do not work against one another and are aligned with the overall economic plan of the country.
Keywords: 330; natural resources; natural resource management framework; sustainable development